System Dynamic Approach to Support Decision in Maintaining Water Availability (Case Study in Aek Silang Sub-Watershed, the Lake of Toba) - Irwan Valentinus Sihotang; S Sudarmadji; Ig.L. Setyawan Purnama; Muhammad Baiquni (Forum Geografi, 2016)
Water availability is immensely affected by the correlation among land use change, rainfall change, and population growth. One of analysis tools to discover how the correlation goes on in a hydrological process is by dynamic modelling approaching. The dynamic modelling result can be used for a substructure in decisions making as supports to maintain water availability for fulfilling domestic needs, agriculture, and Micro-Hydro Power (MHP). The aims of this study are to evaluate water availability as a long-term impact on land use change, rainfall change, and population growth with dynamic modelling and as a scenario which is required as basic information to make decisions in maintaining water availability. Analysis method which is applied in this study is dynamic modelling to long term evaluate water availability and validate using Mean Average Percentage Error method (MAPE). The analysis showed that the combination of rainfall of 2312.09 mm/yr, rainfall intensity of 0.340 mm/h, population growth rate of 7.23%, declined forest area of 1.513 ha/yr, declined shrub/unproductive land of 318.113 ha/yr, increased agricultural land of 7.627 ha/yr, and increased settlement area of 0.473 ha/yr, yielded the estimation of the fail in sustaining water sources in 2090 or the next 79 years from 2011 since the water deficit has reached approximately 3,249,881.02 m3. The value of validation modelling with MAPE method is 8.90, it is a dynamic modelling which is managed nearly the same with actual condition.